Laser welding of NiTi shape memory alloy wires and tubes for multi-functional design applications. (11th July 2016) - Zeng, Zhi; Yang, Mao; Oliveira, João Pedro; Song, Di; Peng, Bei
Abstract: Welding and joining of NiTi shape memory alloys is essential for their integration into an increasing variety of applications. Almost all manufacturers and a significant number of researchers focus their investigation on welding NiTi, which can present both pseudoelasticity (PE) and shape memory effect. Integration of these materials would provide increased flexibility in terms of smart design, in particular for multi-functional systems. The current work investigates the mechanical, physical and phase transformation properties of similar (base materials (BMs) with the same composition) and dissimilar (BMs with different compositions) NiTi welded shape memory wires. The similar and dissimilar welded joints were successfully achieved by laser welding, which can reach up to 88.4% and 67.5% of the wire BM ductility. The joint break force of the similar and dissimilar joints were of 77.2% and 71.4% of the wire BM, respectively. Moreover, laser welding was found to effectively preserve the PE on the similar welded structures. The residual plastic strain variation of the dissimilar welded specimens at different temperatures during the cycling test may be helpful for design of multi-functional or flexible monolithic structures.